2017
DOI: 10.1167/iovs.17-21778
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and Surrogate Endpoints in Drug Development: A European Regulatory View

Abstract: There are several ocular conditions for which there is an unmet medical need. In some of these conditions, surrogate endpoints as well as new clinical endpoints are needed to help speed up patient access to new medicines. Interaction with European regulators through the pathway specific for the development of biomarkers or novel methods is encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 22 publications
0
41
0
2
Order By: Relevance
“…1,2 The emergence of precision medicine and high throughput precision technologies elevated aspirations for defining novel biomarkers that would accelerate improved treatment of diverse adverse health conditions by facilitating the identification of responders to promising novel or repurposed therapeutic strategies. 3,4 A cursory review of the medical literature [5][6][7] over the past 3 decades revealed the emergence of an increasing number of biomarker candidates. However, the exponential rate of initial discovery has now completely outpaced the ability of the biomedical community to successfully develop and validate the clinical utility of prospective biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The emergence of precision medicine and high throughput precision technologies elevated aspirations for defining novel biomarkers that would accelerate improved treatment of diverse adverse health conditions by facilitating the identification of responders to promising novel or repurposed therapeutic strategies. 3,4 A cursory review of the medical literature [5][6][7] over the past 3 decades revealed the emergence of an increasing number of biomarker candidates. However, the exponential rate of initial discovery has now completely outpaced the ability of the biomedical community to successfully develop and validate the clinical utility of prospective biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Following the 2016 Endpoints Workshop on Age-Related Macular Degeneration and Inherited Retinal Diseases organized by the National Eye Institute (NEI, National Institute of Health, USA) and the United States Food and Drug Administration (FDA), it was noted that structural candidate endpoints require evident strong correlations with functional biomarkers in order to become accepted trial endpoints [12]. Patient-reported outcomes were proposed as meaningful secondary outcome measures for future trials in AMD by regulatory agencies and therefore should also be considered [45]. Despite available data on functional, structural, and patient-reported outcome measures in iAMD, surrogate biomarkers require careful validation to avoid potential harm as seen by regulators [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Surrogate endpoints are required in many slowly progressive diseases or when events of interest occur rarely or are difficult to capture [ 43 ]. They have been widely used in clinical trials in ophthalmology with, for instance, intraocular pressure being one of the most common endpoints in glaucoma trials [ 44 , 45 ]. In AMD clinical trials, only high-luminance, high-contrast best-corrected visual acuity has been available as a regulator accepted primary efficacy outcome measure for the approval of new therapeutics in ophthalmology [ 45 ], an outcome measure inapplicable to earlier AMD stages.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, we are unable to pinpoint individual local markers to a particular anterior-posterior location in OCT A-scans, and therefore the exact origin of the feature activation is yet unknown. Nevertheless, biomarker discovery such as reported here may become an important aspect in medical image interpretation as conventional markers are regarded to have substantial weaknesses in reflecting patient-centered outcomes (such as visual acuity), and pivotal drug developments fail presumably also due to the lack of reliable endpoints 15,16 .…”
Section: Discussionmentioning
confidence: 99%